Angiotensin System Autoantibodies Correlate With Routine Prognostic Indicators for COVID-19 Severity - Labandeira, Carmen M.; Pedrosa, Maria A.; Suarez-Quintanilla, Juan A.; Cortes-Ayaso, María; Labandeira-García, José Luis; Rodríguez-Pérez, Ana I. (Frontiers in Medicine, 2022)
Objective: We previously showed that angiotensin type-1 receptor and ACE2 autoantibodies (AT1-AA, ACE2-AA) are involved in COVID-19 outcome and correlate with disease severity. Our aim is to find correlations of autoantibodies with routine biochemical parameters that allow an initial classification of patients. Methods: In an initial cohort of 119 COVID-19 patients, routine parameters tests and serum AT1-AA and ACE2-AA concentrations were obtained in 24 hours after diagnosis, together with clinical data and disease outcome. A Random Forest algorithm was used to select prognostic indicators and the Spearman coefficient for correlations with autoantibodies. Results: Hemoglobin, lactate dehydrogenase and procalcitonin were selected. A decrease in one unit of hemoglobin, an increase in 0.25 units of procalcitonin, or an increase in 100 units of lactate dehydrogenase increased the severity of the disease by 35.27%, 69.25% and 3.2% respectively. Our binary logistic regression model had a predictive capability to differentiate between mild and moderate/severe disease of 84%, and between mild/moderate and severe disease of 76%. Furthermore, the selected parameters showed strong correlations with AT1-AA or ACE2-AA, particularly in men. Conclusion: Hemoglobin, lactate dehydrogenase and procalcitonin can be used for initial classification of COVID-19 patients in the admission day, and potential severity subsequently confirmed with AT1-AA and ACE2-AA levels.